Leishmania donovani infection in Eastern Sudan: Comparing direct agglutination and rK39 rapid test for diagnosis-a retrospective study - Elfadil Abass (Asian Pacific Journal of Tropical Medicine, 2020)
Objective: To compare diagnostic accuracy and agreement between direct agglutination test and rK39 rapid tests for diagnosis of visceral leishmaniasis in an endemic area, the Doka area in Eastern Sudan. Methods: Stored sera of confirmed visceral leishmaniasis cases, unconfirmed visceral leishmaniasis-suspects and negative controls were tested by direct agglutination test and rK39 rapid test. The sera were collected from the Doka area in Eastern Sudan. Diagnostic accuracy of direct agglutination test and rK39 rapid test was assessed in terms of sensitivity, specificity, positive predictive value and negative predictive value, estimated at 95% confidence interval (CI). Agreement between the two tests was determined by the kappa (κ) value. Results: Taking lymph node aspiration of Leishmania as a gold standard, direct agglutination test showed 91.0% sensitivity, 99.3% specificity, resulting in a positive and negative predictive value of 99.3% and 91.0%, respectively. In contrast, the sensitivity of rK39 rapid test was 85.2% and specificity 98.6%, resulting in a positive and negative predictive value of 98.5% and 85.9%, respectively. Most (81.3%) of the confirmed visceral leishmaniasis sera revealed strong antibody titers (≥1:6 400). Some sera (n=5) that were positively tested with rK39 rapid test were negative in direct agglutination test (≤1:800); in contrast, direct agglutination test was positive in 12 confirmed visceral leishmaniasis sera that were negatively tested with rK39 rapid test. There was moderate to good agreement between direct agglutination test and rK39 rapid test for confirmed visceral leishmaniasis patients (κ=0.42, 95% CI=0.21-0.63) and control sera (κ=0.80, 95% CI=0.41-1.00). Conclusions: Both direct agglutination test and rK39 rapid test are satisfactory test systems for visceral leishmaniasis diagnosis in East Sudan. Their simplicity makes them ideal for first healthcare in rural areas. These data are relevant also for other East African endemic countries because of the geographical and ...